WAYS OF INNOVATIVE DEVELOPMENT OF AGRICULTURE AND IMPROVEMENT OF PRODUCT COMPETITIVENESS IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article explores innovative development of agriculture and ways to increase product competitiveness in the digital economy. Also, the factors affecting the  sustainable  development  of  agriculture  through  innovative  activities,  the technological,  technical,  and  organizational-economic  competitiveness  of  the production base in agriculture as a result of assimilation of knowledge and innovations are substantiated in the article.